2018
DOI: 10.3389/fpsyg.2018.02409
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Coordination Disorder: The Importance of Grounded Assessments and Interventions

Abstract: This focused review is based on earlier studies which have shown that both children and adults diagnosed as having developmental coordination disorder (DCD), benefited from sensorimotor therapy according to the method Retraining for Balance (RB). Different approaches and assessments for children and adults in regard to DCD are scrutinized and discussed in comparison to RB which mainly includes (a) vestibular assessment and stimulation (b) assessment and integration of aberrant primary reflexes and (c) assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…For instance, some studies have found a statistically significant correlation between uninhibited PR presence in children over 4 years old and poor physical skills (Chinello et al, 2018;Gieysztor et al, 2018). According to Niklasson et al (2018), PRs should be included for assessment and intervention of DCD. One study (Pecuch et al, 2018) showed that the occurrence of neuromotor disorders and persistent PRs in children with diagnosed psychomotor disorders is common.…”
mentioning
confidence: 99%
“…For instance, some studies have found a statistically significant correlation between uninhibited PR presence in children over 4 years old and poor physical skills (Chinello et al, 2018;Gieysztor et al, 2018). According to Niklasson et al (2018), PRs should be included for assessment and intervention of DCD. One study (Pecuch et al, 2018) showed that the occurrence of neuromotor disorders and persistent PRs in children with diagnosed psychomotor disorders is common.…”
mentioning
confidence: 99%
“…We have argued that a receptive vestibular system is a prerequisite for a proper vestibular function, in order for the primary reflexes to become suppressed, thereby allowing the gross motor milestones to develop. This in turn will prepare the human body for a stable erect position as well as for sensorimotor coordination e.g., [10].…”
Section: Not Neither -Nor Rather a Continuummentioning
confidence: 99%
“…With this commentary our aim is to present further characteristics of this 'psychological barrier,' which we previously have speculated to be associated with vestibular underachievement, an overlooked part in the assessments and interventions of developmental coordination disorder (DCD) [10]. We will discuss the possibility that this by then 'identified psychological barrier' is of prime importance to understand in order for therapists, teachers and trainers to be able to increase the convenience of physical activity and to reduce the risks of developing DCD.…”
Section: Introductionmentioning
confidence: 99%
“…Several gaps in literature were identified in this systematic review. Previously published literature has compellingly mentioned a high prevalence of co-existence of vestibular dysfunctions with these conditions (67,71,(74)(75)(76). However, a substantial deficit in literature was identified in conditions such as TBI and CP for pediatric population groups.…”
Section: Future Directionsmentioning
confidence: 99%